Mapping The Errors in Museum Captions Translation using Coca at Benteng Rotterdam - Sheila Putri Prijayani; Ana Rosida; Bahar (Journal of English Development, 2026)
This study aims to map and analyze translation errors in bilingual museum captions at Museum La Galigo, Fort Rotterdam, by utilizing the Corpus of Contemporary American English (COCA) as a validation tool. COCA serves as the primary research instrument, providing empirical data to assess linguistic naturalness and collocational accuracy. Employing a qualitative descriptive method, the study uses purposive sampling to select ten representative captions from culturally significant artifacts. The findings show that most translation errors are lexical and phraseological rather than grammatical. Many captions contain literal translations and unnatural collocations that reduce semantic accuracy and cultural clarity. COCA verification successfully identifies non-native-like expressions and provides more natural and contextually appropriate alternatives. The study concludes that corpus-based approaches can significantly improve the quality of museum translation by supporting more accurate, natural, and culturally sensitive bilingual captions.